Model-based impact evaluation of new tuberculosis vaccines in aging populations under different modeling scenarios: the case of China - Tovar, Mario; Sanz, Joaquín; Moreno, Yamir (Frontiers in Public Health, 2024)
The slow descent in TB burden, the COVID-19 pandemic, along with the rise of multidrugresistant strains of Mycobacterium tuberculosis, seriously threaten TB control and the goals of the End TB strategy. To fight back, several vaccine candidates are under development, with some of them undergoing the phases 2B and 3 of the development pipeline. The impact of these vaccines on the general population needs to be addressed using disease-transmission models, and, in a country like China, which last year ranked third in number of cases worldwide, and where the population is aging at a fast pace, the impact of TB vaccination campaigns may depend heavily upon the age of targeted populations and with the mechanistic descriptions of the TB vaccines.For these reasons, transmission models need to capture the coupling between TB dynamics and demographic evolution, as well as to be able to accommodate different mechanistic descriptions of TB vaccine protection. In this work, we studied the potential impact of a new TB vaccine in China targeting adolescents (15-19 y.o.) or elderly people (60-64 y.o.), according to varying vaccine descriptions that represent reasonable mechanisms of action leading to prevention of disease, or prevention of recurrence, each of them targetting specific routes to TB disease. To measure the influence of the description of the coupling between transmission dynamics and aging in TB transmission models, we explored two different approaches to comptute the evolution of the contact matrices, which relate to the spreading among different age strata. Our results show that the magnitude of model-based impact estimates substantially depends upon the vaccine profile, and it is also strongly related to the modeling approach chosen to describe the time evolution of contact matrices. In spite of these sources of uncertainty, our results also show, in line with previous modeling works, that elder vaccination is a suitable option in China to reduce the incidence of TB.